Authority of The Notary Honorary Assembly In Construction And Issuance of Recommendations For Inspector Calls - Moh. Saleh; Dyah Chandra Kirana (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
Notaries are public officials appointed by the Government to assist the public in making authentic deeds for civil acts. A position held by a notary has the characteristics that have been regulated in the Law on the Position of a Notary and its Amendments. Notaries are not necessarily immune from the law, it may be possible for him to become a suspect if he fulfills elements and can be prosecuted civilly if he makes a mistake. In the event that the investigator will conduct an investigation of the notary, he will first apply for permission in writing to the regional honorary assembly, which will then be carried out with procedural law procedures in accordance with the Law on Notary Positions. It has been found a case of state administrative law relating to the issuance of a letter of recommendation issued by the honorary assembly of the notary area to be investigated in this legal research. The purpose of this legal research is none other than as a means of increasing knowledge in the field of state administrative law and notary science which is expected to be useful for notaries and legal practitioners. This research is normative legal research using a conceptual approach, legislation and a case approach (referring to a decision that has permanent legal force). The results of this study are: In the framework of the function of supervising the position of a notary, an honorary assembly was formed consisting of elements of the notary, government, and academics. The authority of the honorary assembly is the attribution authority which is an authority born from law. The main task of the notary honorary council is to carry out the guidance of a notary and the obligation to give approval or rejection for the purposes of the investigation and judicial process, for taking a photocopy of the minutes of the deed and summoning a notary to attend an examination related to the notary deed or protocol that is in the notary's storage. The legal product issued by the Honorary Council is in the form of a letter of recommendation containing the rejection or approval of the summons of a notary for the purposes of the investigation and judicial process, for taking a photocopy of the minutes of the deed and summoning a notary to attend an examination related to the deed or Notary Protocol which is in the Notary's custody. The legal product is an act of determination that gives birth to a State administrative decision in accordance with the regulations and the AUPB. That the honorary assembly did not immediately give permission for summons, but first a meeting was held with the notary concerned to hear his statement.